Rancang Bangun Aplikasi Pengelolaan Aset Teknologi Informasi Pada Rumah Sakit Islam Jemursari Surabaya - Sukirno, Sukirno; Tjandrarini, A. B.; Wahyuningtyas, Nunuk (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Islamic Hospital Jemursari Surabaya is one of the agencies that provide health services to the community. In providing health services for the community, the hospital uses information technology to support the activities of the public service. The problems faced today, namely the recording of information technology assets that are still using Microsoft Excel so that the information obtained can not be uptodate and not archived properly. This resulted in the decision by the management to be blocked. Based on these descriptions, the solution to overcome that by using a specialized desktop application that can be directly accessed client server integrated and accommodated to all stakeholders. Asset management application using the straight-line method is used to manage the entire information technology assets ranging procurement, receipt, repair, removal, shrinkage, until removal. The process of implementation and evaluation of a system that has been carried out, indicates that the application of asset management is able to provide information technology assets comprehensive information relating to the procurement, receipt, repair, removal, shrinkage, deletion and reporting of all transactions, and may provide asset reports are quick and precise , which can be used by management in making decisions.